2018
DOI: 10.1177/0040059918770663
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing and Treating Elopement in a School Setting

Abstract: Elopement, or running away from supervised areas, is a dangerous and problematic behavior that compromises the safety of people with disabilities at disproportionately high rates. As such, it is paramount that teachers know how to respond to elopement during school to ensure student safety. Although general safety strategies may be helpful in preventing elopement, they fail to address the factors that trigger elopement. Recent advances in the assessment and treatment of elopement offer strategies that teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…On a practical level, results of the current study, along with those by Betz et al (2013) and Fisher et al (2016), may be useful for practitioners to consider when faced with the need to conduct schedule thinning, in that they may save time by at least probing more extended durations of the S Δ before proceeding through gradual increases that are suggested in some practitioner resources (e.g., Phillips, Briggs, Fisher, & Greer, 2018). Even if FCRs do not remain differentiated (e.g., as with Walter in the current study), we demonstrated the ability to recover differentiation by reversing to the previous S Δ duration.…”
Section: Discussionmentioning
confidence: 75%
“…On a practical level, results of the current study, along with those by Betz et al (2013) and Fisher et al (2016), may be useful for practitioners to consider when faced with the need to conduct schedule thinning, in that they may save time by at least probing more extended durations of the S Δ before proceeding through gradual increases that are suggested in some practitioner resources (e.g., Phillips, Briggs, Fisher, & Greer, 2018). Even if FCRs do not remain differentiated (e.g., as with Walter in the current study), we demonstrated the ability to recover differentiation by reversing to the previous S Δ duration.…”
Section: Discussionmentioning
confidence: 75%
“…Elopement involves a student running away or bolting away from a nonpreferred setting or toward a preferred setting (Phillips et al, 2018). Elopement can be problematic for a student in many ways, as it can lead to potentially dangerous situations including traffic accidents and abduction when the student elopes from a building (Anderson et al, 2015).…”
Section: Behavior Assessment Practicesmentioning
confidence: 99%
“…Methods reported for the assessment of elopement included interviews, observations, and functional analyses (Lang et al, 2009). Phillips et al (2018) provide a more specific protocol for the assessment that includes developing a data collection system, conducting a trial‐based functional analysis, and then using the results to identify an intervention to the function(s) identified through the assessment.…”
Section: Behavior Assessment Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rank-based nonparametric tests used in ANSA, on average, have more power to detect small differences (Siegel, 1957). These tests could prove useful particularly in situations where the problem behavior is very dangerous but occurs at low rates (e.g., pica or elopement; Fisher et al, 1994;Phillips et al, 2018). Moreover, they are also useful for analyzing data that may have outliers-for example, an FA in which one session included bursts of problem behavior that substantially exceeded rates observed in all other sessionsas ranking the data minimizes the impact of outliers.…”
Section: Figurementioning
confidence: 99%